The quasispecies of EV-A71 in Hand, Foot and Mouth Disease (HFMD) patients during the 2003 Sibu, Sarawak outbreak - Fauzziah Dahlan, Sarkawi (Universiti Malaysia Sarawak (UNIMAS), 2015)
Hand, Foot and Mouth Disease (HFMD) is a common childhood illness. Viruses from the enterovirus genus, in particular enterovirus 71 (EV-A71) and other species A enteroviruses, are the most common viruses responsible for HFMD infection. Similar to other RNA viruses, EV-A71 also exist as quasispecies. Quasispecies describe a cloud of viral population in which mutation and selection pressures are at a balance. This occurs when viruses are adapting to environmental changes. In this study, we determined the quasispecies population of EV-A71 genogroup B5 viruses, obtained during a HFMD outbreak in Sibu, Sarawak in 2003. Ten patients with multiple swabs sample with confirmed EV-A71 genogroup B5 were selected for the study. Partial VP1 gene sequence from two separate swab samples from each of the selected patients were cloned. A total of twenty randomly selected colonies with the correct inserts were selected from each sample and subjected to sequencing. These cloned sequences were then compared to a parental consensus sequence generated directly from PCR of the primary clinical sample. Sequence differences observed between cloned product and parental PCR product suggest quasispecies diversity of EV-A71 for that sample. The three sample types studied included throat, rectal and vesicle swab samples. Ten percent of the cloned-derived colonies were identified with nucleotide change. About a third of the nucleotide changes led to a silent mutation during protein translation. No correlation was observed between quasispecies diversity and the phenotype of the virus as determined by ough the cloned-derived colonies in the vesicles swab samples are variants instead of clonal, the percentage of the cloned-derived colonies with amino acid change is only 6.7% which is the lowest compared to the other two sample types